High energy efficient ultra-low voltage SRAM design : device, circuit, and architecture - Kim, Tony Tae-Hyoung (2013)
High energy efficient ultra-low voltage SRAMs play a key role in many emerging ultra-low power applications. However, design of SRAMs for reliable ultra-low voltage operation is challenging due to various problems. In this paper, we explore various ultra-low voltage SRAM design techniques for improving energy efficiency. Effect of MTCMOS on energy efficiency improvement, circuit techniques for ultra-low voltage operation, and architectural considerations will be presented.